2006
DOI: 10.1073/pnas.0609012103
|View full text |Cite
|
Sign up to set email alerts
|

A Legionella pneumophila -translocated substrate that is required for growth within macrophages and protection from host cell death

Abstract: Legionella pneumophila requires the Dot/Icm protein translocation system to replicate within host cells as a critical component of Legionnaire's pneumonia. None of the known individual substrates of the translocator have been shown to be essential for intracellular replication. We demonstrate here that mutants lacking the Dot/Icm substrate SdhA were severely impaired for intracellular growth within mouse bone marrow macrophages, with the defect absolute in triple mutants lacking sdhA and its two paralogs. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
241
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(256 citation statements)
references
References 47 publications
12
241
0
3
Order By: Relevance
“…Consistent with this hypothesis, two recent studies showed that a large number of antiapoptotic genes were induced in cells infected by virulent L. pneumophila strains via the activation of the multifunctional transcriptional regulator NF-B (17,18). Moreover, the Dot/Icm substrate SdhA was recently shown to be required for protecting macrophages from cell death by a yet-unknown mechanism (19). In this study we present evidence that the Dot/Icm system substrate SidF (20) is involved in inhibition of host cell death during L. pneumophila intracellular growth in permissive macrophages, at least in part by directly interacting with and neutralizing the activities of two pro-death members of the Bcl2 protein family.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Consistent with this hypothesis, two recent studies showed that a large number of antiapoptotic genes were induced in cells infected by virulent L. pneumophila strains via the activation of the multifunctional transcriptional regulator NF-B (17,18). Moreover, the Dot/Icm substrate SdhA was recently shown to be required for protecting macrophages from cell death by a yet-unknown mechanism (19). In this study we present evidence that the Dot/Icm system substrate SidF (20) is involved in inhibition of host cell death during L. pneumophila intracellular growth in permissive macrophages, at least in part by directly interacting with and neutralizing the activities of two pro-death members of the Bcl2 protein family.…”
supporting
confidence: 52%
“…Transcription of a number of pro-death genes, including the BH-3-only protein BNIP3 and many caspases, also was elevated in response to intracellular growth of the bacterium (17). The induction of pro-death genes poses a problem for infected cells because these proteins sensitize cells to environmental insults, which, during L. pneumophila infection, can be represented by intracellular growth of the bacterium or the translocation of toxic substrates into host cells (19). Here we present evidence that the bacterial protein SidF interferes with host cell death by directly interacting with and inhibiting activities of apoptotic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Another modular protein is SdhA/Lpg0376, a Dot/Icmsecreted virulence factor that contains a GRIP and a coiled-coil domain (Table 2). SdhA is required for growth within macrophages and protection from host -cell death (Laguna et al 2006). Furthermore, the Legionella-containing vacuole is actively stabilized by the SdhA protein during intracellular replication, which affords the bacterium protection from cytosolic host factors that degrade bacteria and initiate immune responses (Creasey and Isberg 2012).…”
Section: Eukaryotic-like Proteins Of Legionella Are Virulence Factorsmentioning
confidence: 99%
“…The icm/dot type IV secretion system is the major virulence system known in L. pneumophila; this system consists of 26 Icm/Dot proteins that probably constitute the secretion complex itself, as well as accessory proteins, such as chaperones (for a review, see reference 49). In the last 5 years, a growing number of protein substrates (RalF, LidA, Lep, Sid, Vip, Wip, Ylf, Leg, Vpd, Drr, and Ceg) that are translocated into host cells via the icm/dot secretion system were identified (for a review, see reference 42); in most cases the function of these proteins is not known, but two of them (SidF and SdhA) were shown to be required for inhibition of host cell death (5,27) and four others (RalF, LidA, DrrA/SidM, and SidJ) were shown to be required for manipulation of host cell vesicular trafficking (28,31,37,38), as well as other functions (11). Even though many icm/dot genes and many more icm/dot translocated substrates (IDTS), as well as potential IDTS, have been identified, there is only a limited amount of information about direct regulators that control the levels of expression of these genes.…”
mentioning
confidence: 99%